Pengembangan Media Pembelajaran Visual Novel â€œPlus And Minusâ€ Berbasis Smartphone untuk Materi Bilangan Bulat SMP - Achsanudin Nursy; Atik Wintarti; Nina Rinda Prihartiwi (Program Studi S1 Matematika UNESA, 2023)
In the current technological era, the use of technology is important in the world of education.Trends in Mathematics and Science Study (TIMSS) 2019 showcases the importance of using learning technology to increase the effectiveness of learning and teaching. Educators need to make adjustments to develop the quality of learning by using technological media in learning. One of them is by using a smartphone. Thus it is necessary to develop media-based learningsmartphone. The purpose of this research is to find out the process and results of the development of instructional media